New Product Development effect on Venture Sustainability in Ethiopia: Literature review and Factor Analysis Pragmatism - Shashi Kant; Gada Gizachew Wakjira (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
The purpose of the study was to determine how New Product Development Strategies significantly impact Managerial Venture Sustainability. The case of Bule Hora University, Ethiopia, and the research philosophy of research paradigms that must be designed in quantitative and deductive research approaches, researchers have used an exploratory factor analysis (EFA), research design, stratified sampling techniques, and simple random sampling techniques, as well as a method of data collection from academic staff, administrative staff, and university customers. The data analysis was to describe the information that can be analyzed from the exploratory factor analysis, based on the correlation matrix, KMO, average variance extracted, factor loading, rotation matrix analysis, scatter plot, and construct the internal consistency of convergence validity. And it was founded that Strategies for New Product development have an effect on Venture Sustainability in Ethiopia. Therefore, policymakers should focus more on Strategies for New Product Development and Venture Sustainability.